Twentieth annual AGU hydrology days: conference program and abstracts - American Geophysical Union, author; Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2000)
To access abstracts, please see: http://hydrologydays.colostate.edu/program.htm.
AGU hydrology days 2000
Twentieth annual AGU hydrology days was held in the Cherokee Park Room, Lory Student Center, Colorado State University on April 3-6. 2000.
Keywords: Hydrology -- Congresses